PRIOR DETECTION OF ALZHEIMER’S DISEASE WITH THE AID OF MRI IMAGES AND DEEP NEURAL NETWORKS - S A, Karthik; Nandihal , Priya; K, Seemanthini; D R , Manjunath; Liyakathunisa (Malaysian Journal of Computer Science, 2022)
Alzheimer’s disease is a degenerative disease in which brain cells die and deteriorate. It is the most prevalent reason for dementia, which is defined as a progressive decrease in thinking, conduct, and social skills that impairs a person’s capacity to operate independently. Although it is fatal the early diagnosis of Alzheimer’s can be extremely helpful. Our main aim is to help with the diagnosis of this disease in its early stages using the VGG16 classifier which is a convolutional neural network (CNN) that is 16 layers deep. The dataset consists of MRI images of the brain. Data augmentation is done to significantly increase the diversity of data available and Data pre-processing helps to enhance the overall truthfulness of the proposed approach.